Evaluación del coagulante-floculante natural de Aloe Vera en aguas residuales - Florez Cala, Brisabeth Paola (2025)
The present research aimed to reduce turbidity and total suspended solids in wastewater from the Sicuani Wastewater Treatment Plant (PTAR), located in Cusco, through the use of an Aloe vera-based coagulant-flocculant, with the goal of improving the quality of the treated effluent. The main objective of the study was to determine the optimal dose of Aloe vera to maximize the reduction of turbidity and total suspended solids during the effluent treatment process. An experimental laboratory study was conducted using the jar test method, in which Aloe vera was applied in three different forms: powder, diluted, and blended. The tested doses were as follows: powder (0.3 g/L, 0.35 g/L, and 0.4 g/L), diluted (5 mL/L, 10 mL/L, and 15 mL/L), and blended (5 mL/L, 10 mL/L, and 15 mL/L). Subsequently, the efficiency of the coagulant-flocculant was evaluated by analyzing the percentage reduction of turbidity and suspended solids later to the sedimentation stage. The results showed that the treatment with powder (0.35 g/L) achieved a 43.58% reduction in turbidity and 61.22% in TSS. When using the diluted solution (5 mL/L), efficiency increased to 51.93% in turbidity and 67.34% in TSS, while the blended solution (10 mL/L) reached 55.92% turbidity removal but showed a slight decrease in TSS reduction (53.06%). These results indicate that the diluted solution (5 mL/L) was the most effective for TSS reduction, while the blended solution (10 mL/L) performed best in reducing turbidity. In conclusion, Aloe vera proved to be an effective coagulant-flocculant for improving the quality of wastewater treated at the Sicuani PTAR, providing a solid foundation for future applications and process optimization.